(untitled) (Journal of the College of Basic Education, 2023)
No one has succeeded in saying that Yemen, including the city of Hodeidah, was not affected by the events of the First World War, as a result of its neutral position, or its distance from the main battlefield in Europe or in the Near East region, so whoever looks at the details of this research feels that the Yemeni people have lost hundreds. Of his sailing boats that were known as (Dawa) and their homes and facilities on the coast, which are all properties of the Yemeni community, especially the people of the coastal city of Hodeidah, whose land was a large field for many battles, which resulted in the whole country suffering from The maritime blockade and thus the economic blockade imposed on the country in general, had its repercussions on the city of Hodeidah and its negative effects, as a result of its central geographical location and economic wealth, so the Yemeni people suffered many of these events and their developments throughout the stage of the First World War.